Impacts of Board Characteristics on Corporate Performance: Evidence from Bangladeshi Listed Companies - Mofijul Hoq Masum; Maksudur Momin Khan (International Business and Accounting Research Journal, 2019)
The purpose of this study is to investigate the impacts of board characteristics on corporate performance. To conduct this study one hundred and one Bangladeshi listed companies are taken into consideration. Simultaneous multiple regression analysis has been used to address the relationship between the proxy variables of board characteristics and the proxy variable of corporate performance. The study revealed that out of five proxy variables of board characteristics, board member’s ownership and foreign member on board has significant positive relationship on corporate performance whereas the other three proxy variables of board characteristics - board size, percentage of independent director on board and percentage of women on board has no statistical significant association along with corporate performances of the selected companies. Implications: The findings of the study portrays the scenario of board characteristics and its influence on corporate performance which certainly will pave the way to encourage the corporate people to take life-sustaining decisions regarding board members. These results also provide immense opportunity to the future researchers regarding to the exploration of the association between various attributes of board characteristics and levels of corporate performance.